Implementasi Maqāṣid Syarī’ah dalam Praktik Parenting pada Komunitas Kepompong di Sekolah Sahabat Alam Palangka Raya - Rismanto, Ikbal Reza; Soeradji, Elvi; Emzaed, Ali Murtadho (Muhammadiyah University of Surabaya, 2024)
In the midst of the rampant divorce that occurs in Palangka Raya, Kepompong Community is present to provide parenting practice services for its members. This study aims to examine the extent of maqāṣid syarī'ah implementation in parenting practices conducted by Kepompong Community at Sekolah Alam Palangka Raya. This juridical-empirical research uses a conceptual approach to examine the description of parenting practices in the community. The source of data is from interviews with resource persons, among others: the initiator of the Kepompong community and members of the Community and teachers of Sekolah Sahabat Alam. The results showed that the parenting program conducted by Kepompong Community is a parenting seminar by experts, family consultation and family gathering. The purpose of the program is to understand the members about parenting patterns and realize the importance of creating a harmonious family, as well as building an environment full of togetherness. From these activities, it can be seen how the community contributes to guiding families towards the concept of sakinah, which is in line with the maqāṣid syarī'ah, namely the protection of religion, soul, offspring, mind and property. Thus, Kepompong Community's parenting practices can be used as a model by other communities so that harmonious families can be realized. In addition, collaborating institutions such as Pusaka Sakinah, Komnas Perempuan and DPPPA are expected to take part in facilitating parenting practices for the community considering the urgency of these activities because harmonious families are the foundation of a strong state.